2009
DOI: 10.1111/j.1467-8624.2009.01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure to Parents About Everyday Activities Among American Adolescents From Mexican, Chinese, and European Backgrounds

Abstract: Disclosure to parents and reasons for not disclosing different activities were examined in 489 Chinese, Mexican, and European American adolescents (M = 16.37 years, SD = 0.77). With generational status controlled, Chinese American adolescents disclosed less to mothers about personal and multifaceted activities than European Americans and less about personal feelings than other youth, primarily because these acts were considered personal, not harmful, or because parents would not listen or understand. Disclosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
119
2
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 50 publications
(136 reference statements)
12
119
2
5
Order By: Relevance
“…While parents reflected on their adolescents' secretiveness, it was observed that parents felt frustrated when adolescents were secretive about their activities, as the parents had to increase their efforts to gain information from other sources. Consistent with earlier research (Kerr et al, 2010:39;Yau et al, 2009Yau et al, :1492, this study established that parental knowledge of adolescents' activities depended more on adolescent self-disclosure than parental solicitation. The parents participating in this study reported that adolescents would at times share information about their activities out of their own volition; however, most reported that their adolescents would not share information voluntarily.…”
Section: Sub-theme 31: Parents' Direct Monitoring Methodssupporting
confidence: 90%
See 3 more Smart Citations
“…While parents reflected on their adolescents' secretiveness, it was observed that parents felt frustrated when adolescents were secretive about their activities, as the parents had to increase their efforts to gain information from other sources. Consistent with earlier research (Kerr et al, 2010:39;Yau et al, 2009Yau et al, :1492, this study established that parental knowledge of adolescents' activities depended more on adolescent self-disclosure than parental solicitation. The parents participating in this study reported that adolescents would at times share information about their activities out of their own volition; however, most reported that their adolescents would not share information voluntarily.…”
Section: Sub-theme 31: Parents' Direct Monitoring Methodssupporting
confidence: 90%
“…Consistent with previous research (Tolou-Shams, Hadley, Conrad & Brown, 2012:449-456;Yau et al, 2009Yau et al, :1493, the parent-adolescent relationships in this study were affected by the adolescents' clash with the law, and most parents reported not being sure as to whether they could trust their adolescents, hence the imposition of restrictions on their adolescents' freedom. Parents reported that their relationships with their spouses or ex-spouses had been negatively affected by their adolescents' arrest and diversion.…”
Section: Sub-theme 33: Parents' Experiences Of Implementing the Monisupporting
confidence: 86%
See 2 more Smart Citations
“…El motivo para no comunicar sus actividades es la percepción de que se trata de actividades privadas, que no causan daño a nadie y que sus padres no les escucharían o entenderían (Yau, Tasopoulos-Chan y Smetana, 2009).…”
Section: Adaptación Y Aculturación De Los Inmigrantes Y Sus Hijos En unclassified